Comparative Analysis of Public Policies and Best Practices of Transparency in Ecuador 2004-2014 - Jara Iñiguez, Irma (Revista del CLAD Reforma y Democracia, 2017)
The American States during the 2000s adopted several principles in the area of ​​transparency and access to information. To achieve change their practices has been necessary to develop the respective institutional frameworks and implement actions to ensure their effectiveness in a digital age, which in turn has increased the demand for information from the citizens. In Ecuador, from May 2004, it has Organic Law of Transparency and Access to Public Informatio; in February 2007 declared as a State policy the combat against corruption in public administration, and in 2008 with the new Constitution of the Republic, the Function of Transparency and Social Control, among others, is created to protect the exercise and enforcement of rights, prevent and combat corruption and to promote and encourage citizen participation. This is a case study about Ecuador for the period 2004-2014, which analyzes the progress and degree of coherence between the rules and instruments developed and actions implemented from the State Institutions, regarding transparency in public administration. It identifies best practices and contrasts with the results obtained in international measurements. It was used a qualitative and documentary analysis, with a scheme based on a diachronic comparison. Two phases were determined, taking into account as relevant aspect the Constitutional changes, and these as a essential context for the public actions and the institutional changes made. The identification of best practices is made on the basis of an analysis and valuation in binary form, being mainly: technical instruments homologated, technological systems of varying complexity, creation of public spaces for citizen participation, community spaces, inclusive regulations, codes of ethics, accessibility and training. It is evident that as the institutional framework is developed and the mechanisms and tools of government transparency are strengthened, the perception of corruption decreased slightly. The research efforts subsequent to this article may focus on outcomes in terms of the sustainability of good practices and its relation with the perception of corruption.